William David Coolidge papers - Coolidge, William David, 1873-
Chiefly speeches (1940-1954) relating to roentgenology (radiology)
Physicial chemist and roentgenologist (radiologist)
Collection material in English.
Keywords: Radiology, Medical; Chemists; Radiologists